Molecular mechanisms regulating wound repair: Evidence for paracrine signaling from corneal epithelial cells to fibroblasts and immune cells following transient epithelial cell treatment with Mitomycin C - Pal Ghosh, Sonali (2023)
In this paper, we use RNAseq to identify senescence and phagocytosis as key factors to understanding how mitomyin C (MMC) stimulates regenerative wound repair. We use conditioned media (CM) from untreated (CMC) and MMC treated (CMM) human and mouse corneal epithelial cells to show that corneal epithelial cells indirectly exposed to MMC secrete elevated levels of immunomodulatory proteins including IL-1α and TGFβ1 compared to cells exposed to CMC. These factors increase epithelial and macrophage phagocytosis and promote ECM turnover. IL-1α supplementation can increase phagocytosis in control epithelial cells and attenuate TGFβ1 induced αSMA expression by corneal fibroblasts. Yet, we show that epithelial cell CM contains factors besides IL-1α that regulate phagocytosis and αSMA expression by fibroblasts. Exposure to CMM also impacts the activation of bone marrow derived dendritic cells and their ability to present antigen. These in vitro studies show how a brief exposure to MMC induces corneal epithelial cells to release proteins and other factors that function in a paracrine way to enhance debris removal and enlist resident epithelial and immune cells as well as stromal fibroblasts to support regenerative and not fibrotic wound healing.